2003
DOI: 10.1161/01.cir.0000086322.21781.6a
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Angioplasty for Acquired Pulmonary Vein Stenosis After Radiofrequency Ablation

Abstract: Background— Pulmonary vein stenosis has recently been recognized as a complication of radiofrequency ablation for atrial fibrillation. This study evaluates the presentation of affected patients and the role of transcatheter therapy for this patient population. Methods and Results— This study used a retrospective review of data from 19 patients (age, 51±13 years) with pulmonary vein stenosis who underwent catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(82 citation statements)
references
References 45 publications
1
79
0
2
Order By: Relevance
“…4 Percutaneous intervention for PVS after PVI has been reported by several groups, all with relatively small numbers of patients and short to mid-term follow-up. [12][13][14][16][17][18] This study describes mid-to long-term outcomes of percutaneous intervention for the largest number of patients with PVS after PVI reported to date. It has been previously shown that for veins displaying close to normal or normal upstream diameter, stent implantation is superior to balloon dilation, with significantly higher re-intervention rates for the latter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Percutaneous intervention for PVS after PVI has been reported by several groups, all with relatively small numbers of patients and short to mid-term follow-up. [12][13][14][16][17][18] This study describes mid-to long-term outcomes of percutaneous intervention for the largest number of patients with PVS after PVI reported to date. It has been previously shown that for veins displaying close to normal or normal upstream diameter, stent implantation is superior to balloon dilation, with significantly higher re-intervention rates for the latter.…”
Section: Discussionmentioning
confidence: 99%
“…The catheterization procedure has been previously described in detail. 16 Pulmonary artery wedge angiography was performed to visualize the stenotic vein on levophase prior to transseptal puncture ( Figure 1). Very early in the experience, balloon angioplasty was always performed as the first intervention regardless of upstream diameter, but soon thereafter, primary stenting was performed in larger vessels.…”
Section: Pulmonary Vein Intervention and Periprocedures Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 An important point emphasized by this case is the discrepancy between the initial diagnosis provided by CT scan versus catheterization with conventional angiography: despite a CT scan suggesting LLPV atresia, angiography found that there was indeed pinhole patency of the LLPV, permitting catheter-based intervention. That pinhole patency of PVs can be missed by CT angiography has been previously described, 11 and highlights a number of advantages of conventional angiography over CT, such as higher spatial and temporal resolution, and the ability of pulmonary artery wedge angiography to force contrast through a pinhole PV ostium that might not be visible by…”
Section: Discussionmentioning
confidence: 70%
“…Accidental total thrombosis of both pulmonary veins after ablation for AF may be misdiagnosed for 8-16 weeks [2,4]. The main symptoms of this complication such as shortness of breath, excertional dyspnea, and hypoxemia are usually attributed to the antecedent heart operation and/or to the pre-existent congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%